Pengembangan produk sambal roa inovatif melalui formulasi undur-undur laut: The development of innovative sambal roa product through mole crab formulation - Bambang Riyanto; Utami Dyah Syafitri; Wini Trilaksani; Immatul Ulya (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
Sambal roa is one of the typical nusantara sauces with a distinctive taste and aroma of roa fish smoked using traditional methods. The decreasing production of roa fish demands innovation in its product development. Mole crab is a potential substitute ingredient because it has a crustacean/rebon taste similar to shrimp paste, as well as carotenoid content that can act as a natural dye. This innovation requires accurate formulation. This study aimed to develop an innovative sambal roa product through the formulation of chili, smoked roa fish, and mole crab using an I-optimal mixture amount design. The study included modification, production, and descriptive sensory testing of sambal roa, optimization of the sambal roa formulation with mole crab, and comparison between mole crab-sambal roa and commercial sambal roa. The sambal roa formula is based on a total mixture amount of 150 g with a proportion of chili of 40%-70%, smoked roa fish of 20%-30%, and mole crab of 35%-50%. Optimal acceptability was achieved with chili 40%, 21.68% smoked roa fish, and mole crab 38.32%. The characteristics of the innovative sambal roa with the formulation of chili, smoked roa fish, and mole crab are in the form of paste, have a viscosity of 9.547±948.54 cP, an orange-red color with L*:19.64±0.76, a*:17.58±0.80, and b*:22.75±0.68. The distinctive crustacean aroma (mole crab) can be sensed, and it has a spicy sensation with a capsaicin content of 701.78±0.028 ppm, protein content of 11.32±0.007%, fat content of 15.28±0.049%, water activity (Aw) of 0.84±0.0001, and total bacterial colonies of 6.3 ×10²±1.90 colonies/g.